RESPON PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rappa L.) TERHADAP BERBAGAI DOSIS KOMPOS TPS3R BAKTISERAGA PADA SISTEM URBAN FARMING - Imam Busyairi; Putu Shantiawan Prabawa; Made Suarsana (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
One type of vegetable plant that has high benefits and economic value is mustard greens or pakcoy. Although production is still quite high, productivity shows a decline. This is due to the narrowing of agricultural land, so that people's need for food is decreasing. The urban farming plant cultivation system by utilizing limited home yard areas makes the use of polybags absolutely necessary. There needs to be testing for the dose of compost needed to influence the growth and yield of pakcoy plants using compost produced by TPS3R Baktiseraga Village with raw materials originating from household waste in the form of kitchen waste and leaf waste. Based on the results of the study, the treatment of various doses of household compost from TPS3R Baktiseraga Village had a significant effect on the parameters of plant height, root length, total fresh weight, and total dry weight of plants. The treatment of a compost dose of 100 g.polybag-1 showed the highest results in the parameters of plant height, root length, total fresh weight, and total dry weight of plants. Keyword: , ,